2003
DOI: 10.1016/s1521-6616(03)00147-5
|View full text |Cite
|
Sign up to set email alerts
|

CCR5 promoter polymorphism determines macrophage CCR5 density and magnitude of HIV-1 propagation in vitro

Abstract: The common CCR5 promoter polymorphism at position -2459 (A/G) has been associated with differences in the rate of progression to AIDS, where HIV-1-infected individuals with the CCR5

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
58
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(61 citation statements)
references
References 32 publications
2
58
1
Order By: Relevance
“…31,33 The implications of these findings require further exploration in this population, since no difference with HESNs was detected.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…31,33 The implications of these findings require further exploration in this population, since no difference with HESNs was detected.…”
Section: Discussionmentioning
confidence: 92%
“…Finally, the GACAT haplotype was more frequent in HC than SP individuals; furthermore, this haplotype contains the 927T allele, which has been associated with slow AIDS progression in SPs and lower probability of becoming infected. 31,33 HHC was more frequent than HHE in the HESNs. Previously, Gonzalez et al reported that white, Asian, and Hispanic American populations exhibited a higher frequency of HHC than HHE, as in our HESN group, but contrary to what was observed in the HC and SP groups.…”
mentioning
confidence: 88%
See 1 more Smart Citation
“…The CCR5 P1 allele, a composite haplotype comprising 13 distinct SNP alleles in the upstream promoter region of CCR5, confers recessive more rapid progression to AIDS 34,35 . Analysis of CCR5 promoter alleles found no quantitative differences in luciferase transcription, HIV-1 binding or HIV-1 infectivity, although the alleles influence CCR5 abundance on lymphoid cells 36,37 . Further, oligonucleotides that define the CCR5 P1 allele showed allele-specific recognition of nuclear transcription factors belonging to the cREL family, a result that suggests, but does not prove, that CCR5 promoter alleles could differentially react and respond to transcription factors in different cell types 37 .…”
Section: Mechanism Of Action For Argsmentioning
confidence: 89%
“…This association is believed to occur because persons homozygous for this haplotype have greater levels of expression of the chemokine receptor and HIV coreceptor, CCR5. 17,18 This high-expressing CCR5 genotype, termed 59029 A/A, 19 P1/P1, 20 Ϫ2459A/A, 21 or HHE/HHE, 22 also has been associated with renal transplantation outcomes. 23 Here we used 4 variants of the CCR5 gene to define the high-expressing haplotype, which in this study we term CCR5 H1.…”
Section: Introductionmentioning
confidence: 99%